Aplikasi Pengukur Similarity Copywriting Penjualan Produk Menggunakan Metode N-Gram Berbasis Web - Muhammad Faried Ikhwan; Devi Yunita (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Marketing is an integral part of the economy in today's society. Marketing by means of marketing communications has spread rapidly as a much needed communication system. Not just for developers, but for all customers. Advertising expertise and methods in providing information to customers is much needed and has an impact on the success of marketing and making a company logo. Therefore, there are more and more business competitors in all business sectors. The final project research made using the N-Gram method is a collection of words that are determined in one paragraph and when calculating N-Grams it is done by moving one word forward (although in making it there is a process of words moving a number of variable words) So the conclusion is the system is in accordance with the needs of the Marketing Team at CV. Surya Putra Trading to use. It's easier for the Marketing Team to access information about copywriting, as well as carry out the process of checking words for writing fashion product advertisements at CV. Surya Putra Trading.